Analisis Pengaruh Iklan, Brand Trust dan Brand Image Terhadap Minat Beli Konsumen Samsung Galaxy di Ponorogo - Ika Susilawati (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2012)
This research background that the current phenomenon android-based phones in Indonesia in controlled by Samsung, whereas before 2010 the master phones in Indonesia is another vendor. Therefore, the purpose of this study was to determine the factors that influence consumers to buy Samsung galaxy in Ponorogo. This research is descriptive quantitative, using three hypotheses. Analysis of the hypothesis in this study uses a linear regression analysis and t-test with SPSS tools. There are two variables in this study; the dependent variable is interest to buy, and the independent variables, namely advertising, brand image and brand trust, which indicated that three independent variables affect the dependent variable. Third in the proposed hypothesis is H1: Variable advertising influence buying interest, H2: Brand Trust variables affect buying interest, H3: Brand Image variables affect buying interest. The result is all the t-test that produced t-table. T-chart in this study was 0.05. Produce t-test H1 and H2 yield 0.000 t-tests 0.001 while the H3 produce 0.004 t-tests. So from all these results the hypothesis is accepted. So in the hope that this study will contribute to the company that buying interest is influenced by various factors, including advertising, brand trust and brand image, so the company will further improve the service and quality of product.